Informing police, why, when, where and how? - Atul K Shah (Wolters Kluwer Medknow Publications, 2016)
Presentation of burn victims involve trauma in suspicious situation. There is inherent responsibility of all citizens, to report incidences of unexplainable nature to the police. Responsibility of a doctor is an extension of the general duty of a citizen. There are some norms, followed by doctor fraternity and the police, which actually are the guiding factors to maintain channel of information between the law enforcing agencies and the doctor. Alternate procedures of informing police are also enlisted.